Comparison of intubation condition and the quality of muscle relaxation between rocuronium and vecuronium using „timing principle“ - Senada Čaušević; Nermina Rizvanović; Belma Pojskić (Medicinski glasnik, 2019)
Aim: To compare the quality of the conditions for endotracheal intubation and muscle relaxation between rocuronium bromide and vecuronium bromide using the ''timing principle'' method for induction in anaesthesia. The "timing principle" includes the administration of muscle relaxants before the hypnotic agent during induction in anaesthesia. Method: Sixty patients who had undergone elective surgery were randomly allocated into two equal groups using muscle relaxants: rocuronium (group R) and vecuronium (group V). The intubation conditions were asse ssed using Cooper's scoring system, based on jaw relaxation, vocal cords position and response to intubation. The quality of muscle relaxation was evaluated by recording the time of clinical weakness, a count of ''train of four'' (TOF) twitches at intubation, the time of loss TOF response and duration of direct laryngoscopy. Results: The intubation conditions were excellent in 100% of patients in the group R versus excellent in 80% and good in 20% of patients in the group V (p<0.05). The time of clinical weakness was statistically significantly shorter in the group R than in the group V (p<0.000). The time of loss of TOF response was statistically significantly shorter in the group R (p<0.000). The absence of TOF twitches (the level of muscle relaxation of 100%) at intubation recorded in 25 (83.3%) patients in the group R versus five (16.7%) patients in the group V (p<0.000). Duration of direct laryngoscopy did not significantly differ between the groups. Conclusion: Rocuronium bromide provides better intubation conditions and greater quality of muscle relaxation than vecuronium bromide using ''timing principle'' technique.
Keywords: direct laryngoscopy; endotracheal intubation; neuromuscular monitoring; onset time; rapid sequence induction; vocal cords